First characterization of prokaryotic utilization of sinking phytodetritus through mesocosm studies and metagenomic approaches in the Ross Sea (Antarctica). - CATELAN, ELENA (2022)
none The Southern Ocean has one of the highest rates of carbon sequestration in the world. The Antarctic Circumpolar Current plays a big role during this process, since it causes upwelling which in turn creates high productivity biological zones along the coasts of Antarctica. A particularly important area is the Ross Sea, as it accounts for 25% of the carbon recycling in the Southern Ocean. During summer, phytoplankton blooms occur and large quantities of organic matter – POM and DOM – are transported from the surface to deeper waters by a process known as the biological pump. The mesopelagic bacterial communities must metabolize the sinking particles in order to sustain the carbon recycling process. However, specific metabolic functions are essential to the capability of degrading the phytodetritus. A metagenomic analysis may provide information about the bacteria responsible for phytodetritus degradation as well as their functional characteristics. Hence, water samples from a series of mesocosm experiments – consisting of an addition of phytodetritus and filtered water from the mesopelagic zone of the Ross Sea – were sequenced and analyzed via a metagenomic approach. The binning procedure yielded a total of 119 MAGs with a completeness higher than 90% and contamination lower than 10%. The most abundant phylum across all samples is Proteobacteria, representing almost half of the population (45.7%). The clades that showed a fast-growing response to the addition of phytodetritus are Gammaproteobacteria and Polaribacter. The functional annotation of these growing MAGs revealed a significantly higher relative abundance of sequences present inside the genome encoding CAZymes and proteases. Within the CAZymes, the most relevant class is the Glycoside Hydrolases (GH). These enzymes are involved in the hydrolysis of glycosides and so can decompose carbon compounds released during algal blooms. These results provide an insight into the underlying bacterial mechanisms that dictate the degradation of organic matter in ...